2020
DOI: 10.3389/fphar.2020.00050
|View full text |Cite
|
Sign up to set email alerts
|

A Relative Bioavailability Study of Two Misoprostol Formulations Following a Single Oral or Sublingual Administration

Abstract: Introduction: Misoprostol (Cytotec) was primarily made for treating gastric ulcers. However today it is mostly used for abortion, treating postpartum hemorrhage, and for induction of labor. The tablet contains 200 µg of misoprostol, yet the dosages used for induction of labor are much smaller (25-50 µg), leading to uncertainty of dosage in daily use.Aim: To evaluate and compare the relative bioavailability of two misoprostol products (Angusta 25 µg and Cytotec 200 µg tablets) administered orally or sublinguall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The World Health Organization (WHO) has included Misoprostol in the list of essential drugs due to its properties and its optimal profile in terms of costs and benefits, thus resulting in an extremely efficient, appropriate and economic drug (14). Misoprostol explicates its action on the cervix by stimulating contractions and facilitating cervical ripening and dilatation (15). An extended bibliography supports the evidence and recommendations that confirm Misoprostol to be superior and more efficient compared to drugs containing PGE2 (16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Misoprostolmentioning
confidence: 62%
“…The World Health Organization (WHO) has included Misoprostol in the list of essential drugs due to its properties and its optimal profile in terms of costs and benefits, thus resulting in an extremely efficient, appropriate and economic drug (14). Misoprostol explicates its action on the cervix by stimulating contractions and facilitating cervical ripening and dilatation (15). An extended bibliography supports the evidence and recommendations that confirm Misoprostol to be superior and more efficient compared to drugs containing PGE2 (16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Misoprostolmentioning
confidence: 62%
“… 9 , 12 , 25 , 26 The CL/F b and V/F b of MPA in our study were consistent with the PKs observed in a recent study comparing bioavailability of two formulations of misoprostol following oral and sublingual administration in full‐term women. 18 Thus, it appears that clearance of MPA in the third trimester of pregnancy is increased compared to non‐pregnant and first‐trimester pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“… 11 Recently, Amini et al reported PKs of two formulations of misoprostol following oral and sublingual administration at term. 18 To our knowledge, no study has compared the PKs of vaginal versus buccal administration of misoprostol for full‐term labor induction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sublingual route was used assuming that it has higher efficacy than vaginal route [5] . It also avoids the first pass effects of gastrointestinal and hepatic systems [6] . while uterine hyperstimulation rates may be the same as vaginal misoprostol [7] .…”
Section: Discussionmentioning
confidence: 99%